The role of Debrecen maize hybrids in competitive production - Forgács, Barnabás (Acta Agraria Debreceniensis, 2006)
I examined the effects of plant density and fertilisation on the yield of the maize hybrid Debreceni 377 SC, developed by the Agrárgazdaság Ltd., using the 3 year data sequence of a long term experiment set up at the Látókép experimental station of DU Center for Agricultural Sciences in years with average precipitation supply. Based on the evaluation of my research results, I found that the application of higher plant densities was more favourable in years with average or higher than average precipitation supply. During the examination of fertilisation effects, it was verified that surplus yield was realised in most cases where smaller fertilisation dosage, 120 kg per hectare active substance was applied.